Strategies for helping families prepare for birth: experiences from eastern central Uganda - Līga Timša; Gaetano Marrone; Elizabeth Ekirapa; Peter Waiswa (Taylor & Francis Group, 2015)
Background: Promotion of birth preparedness and raising awareness of potential complications is one of the main strategies to enhance the timely utilisation of skilled care at birth and overcome barriers to accessing care during emergencies. Objective: This study aimed to investigate factors associated with birth preparedness in three districts of eastern central Uganda. Design: This was a cross-sectional baseline study involving 2,010 women from Iganga [community health worker (CHW) strategy], Buyende (vouchers for transport and services), and Luuka (standard care) districts who had delivered within the past 12 months. 'Birth prepared' was defined as women who had taken all of the following three key actions at least 1 week prior to the delivery: 1) chosen where to deliver from; 2) saved money for transport and hospital costs; and 3) bought key birth materials (a clean instrument to cut the cord, a clean thread to tie the cord, cover sheet, and gloves). Logistical regression was performed to assess the association of various independent variables with birth preparedness. Results: Only about 25% of respondents took all three actions relating to preparing for childbirth, but discrete actions (e.g. financial savings and identification of place to deliver) were taken by 75% of respondents. Variables associated with being prepared for birth were: having four antenatal care (ANC) visits [adjusted odds ratio (ORA)=1.42; 95% confidence interval (CI) 1.10-1.83], attendance of ANC during the first (ORA=1.94; 95% CI 1.09-3.44) or second trimester (ORA=1.87; 95% CI 1.09-3.22), and counselling on danger signs during pregnancy or on place of referral (ORA=2.07; 95% CI 1.57-2.74). Other associated variables included being accompanied by one's husband to the place of delivery (ORA=1.47; 95% CI 1.15-1.89), higher socio-economic status (ORA=2.04; 95% CI 1.38-3.01), and having a regular income (ORA=1.83; 95% CI 1.20-2.79). Women from Luuka and Buyende were less likely to have taken three actions compared with women from Iganga (ORA=0.72; 95% CI 0.54-0.98 and ORA=0.37; 95% CI 0.27-0.51, respectively). Conclusions: Engaging CHWs and local structures during pregnancy may be an effective strategy in promoting birth preparedness. On the other hand, if not well designed, the use of vouchers could disempower families in their efforts to prepare for birth. Other effective strategies for promoting birth preparedness include early ANC attendance, attending ANC at least four times, and male involvement.